COnsensus on Pediatric Pain in the Emergency Room: the COPPER project, issued by 17 Italian scientific societies - Franca Benini; Ilaria Corsini; Emanuele Castagno; Davide Silvagni; Annunziata Lucarelli; Luca Giacomelli; Angela Amigoni; Gina Ancora; Marinella Astuto; Fabio Borrometi; Rosa Maria Casilli; Elena Chiappini; et al. (BMC, 2020)
Abstract In the pediatric setting, management of pain in the emergency department - and even in common care - is a challenging exercise, due to the complexity of the pediatric patient, poor specific training of many physicians, and scant resources. A joint effort of several Italian societies involved in pediatrics or in pain management has led to the definition of the PIPER group and the COPPER project. By applying a modified Delphi method, the COPPER project resulted in the definition of 10 fundamental statements. These may represent the basis for improving the correct management of children pain in the emergency department.